ANTIVIRAL ACTIVITIES OF SUPERNATANT OF FERMENTED MAIZE (OMIDUN) AGAINST SELECTED ENTEROVIRUSES (FUDMA JOURNAL OF SCIENCES, 2023)
Enteroviruses (EVs) are of enormous public health significance being the etiological agents of an array of clinical conditions, local fermented product may confer protection in the gastrointestinal tract against EVs. Omidun (supernatant of fermented maize) has been traditionally used to reduce the frequency of stooling during diarrheal episodes. However, there is no information on the antiviral activities of Omidun on EVs and the scientific proof of the traditional claims. This study, therefore, investigates the antiviral potentials of Omidun against EVs. The antiviral activity of Omidun was determined against Echovirus 7 (E7), E13 and E19 in a pre- and post-treatment approach. The antiviral effect was determined by cytopathic effect and cell viability using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromidefor. (MTT) assay. Omidun had high percentage inhibition for E7 and E19 with 83.5% and 77.9% respectively, in pre-treatment, and 78.2% and 77.5% respectively, in post-treatment. Minimal effects were observed for E13; 12.2% and 24.2% in pre- and post-treatment, respectively. Generally, antiviral activity for pre-treatment was better than post-treatment. Omidun was shown to have the potential to inhibit the replication of selected EVs. Thus, supporting the traditional claims of its therapeutic effect. To the best of our knowledge, this is the first report of antiviral activities of Omidun.
Keywords: Omidun, Human Enterovirus and Antiviral